Something Bigger than Girard - Klawans, Jonathan (Bulletin for the study of religion, 2016)
René Girard's works on religion and violence remain important, above all, for having called attention to the question of religious violence well before the significance of this problem seemed obvious. Despite Girard's insistence on the scientific nature of his project, various religious aspects of his work can be identified, and his work is often treated religiously by his followers. Mimetic theory will have to accept its limitations if it is to win over its critics.